Improvement of chilling efficiency and meat tenderness of broiler carcasses using subzero saline solutions. (2nd April 2019) - Metheny, M M; Lee, H C; Viliani, S; Bennett, D C; Hurley, S; Kang, I
ABSTRACT: Carcass chilling in subzero saline solutions has the potential to improve chilling efficiency and meat quality. The purpose of this research was to investigate the effects of subzero saline chilling on broiler carcass for chilling efficiency and breast tenderness. Broiler carcasses were chilled using 2 high saline solutions (4% NaCl/–2.41°C and 8% NaCl/–5.08°C) without (Experiment I) and with (Experiment II) a pre-chilling step, and 3 low saline solutions (1% NaCl/–0.6°C, 2% NaCl/–1.2°C, and 3% NaCl/–1.8°C) in Experiment III. Ice water slurry (0% NaCl/0.5°C) was used as a control. In Experiments I and II, the breast fillets of broilers in subzero saline solutions showed significantly lower shear forces than those in water control, regardless of salt content and temperature level ( P < 0.05). In Experiment III, 3% NaCl/–1.8°C solution reduced the broiler chilling time by 22% over the water control, with an intermediated reduction (13 to 17%) observed for 1% NaCl/–0.6°C and 2% NaCl/–1.2°C solutions. Shear force was stepwise reduced as the salt concentration increased from 0 to 3% and the solution temperature decreased from 0.5 to –1.8°C. No significant difference was observed for carcass chilling yield, breast pH/R-value, and breast cooking yield/salt content, regardless of chilling method. Based on these results, chilling of boiler carcass in 3% NaCl/–1.8°C or higher NaCl and lower temperature solutions appears to improve carcass chilling efficiency and meat tenderness over the traditional water immersion chilling.